2018 FDA Tides Harvest - Danah Al Shaer; Othman Al Musaimi; Fernando Albericio; Beatriz G. de la Torre (MDPI AG, 2019)
In 2018, the United States Food and Drug Administration (FDA) approved a total of 59 new drugs, three of them (5%) are TIDES (or also, -tides), two oligonucleotides and one peptide. Herein, the three TIDES approved are analyzed in terms of medical target, mode of action, chemical structure, and economics.